Hepatitis B Virus (HBV) Infection and Hepatocellular Carcinoma - New Insights for an Old Topic - Yan, Shi-Yan; Fan, Jian-Gao; Qiao, Liang (Current Cancer Drug Targets, 2017)
Background: Hepatocellular carcinoma (HCC) is the most deadly form of liver cancer. Chronic hepatitis and subsequent liver fibrosis and cirrhosis are the major causes of HCC. HBV infection results not only in HCC but also extra-hepatic cancers. However, the importance and approaches for HCC screening in HBV infected individuals, the risk factors of HCC, the possible mechanisms leading to HCC and the potential therapeutic approaches of HBV-related HCC have less been systematic reviewed. Methods: In this study, we reviewed the screening, risk, new biomarker, mechanism and therapeutic of HBV-related HCC. Results: Serum AFP should be used for the HCC screening in CHB patients. Higher HBV viral load is associated with increased risk of HCC. HBV genotype and genetic polymorphism contribute to the risk of HCC.Ku86, Ku86 antibody, miR-18a, miR-122 and miR-150 may be reliable markers of HBVrelated HCC. MicroRNAs and HBx play a key role in HBV-related HCC. Two types of drugs, conventional interferon (IFN), and nucleoside analogs (NAs), have recently become available for the treatment of CHB infection. However, treatment guidelines for these patients have not yet established. Conclusion: A comprehensive understanding of how HBV infection causes HCC is of great importance in developing more effective antiviral therapy and prevention of late stage consequences such as cirrhosis and HCC. Regular screening in HBV infected individuals is a practically useful approach in reducing the HCC incidence in these patients. More reliable markers for HCC early detection should be explored. Combining IFNs and NAs with other curative approaches have superior benefits in preventing HCC recurrence.
Keywords: serum AFP